Medical Modernization: A Macro Level Conceptualization of Medical Care Programs - Hayes-Bautista, David; Minkler, Meredith (International Review of Community Development / Revue internationale d’action communautaire, 1979)
The authors seek to conceptualize the assumptions underlying the theoretical models of medical modernization. They note that the implantation of a rational and scientific health care system has often meant simply copying western models.The application of medical modernization models is examined in relation to marginal and disadvantaged groups in the United States as well as developing countries. The authors attempt to identify the general characteristics of these programmes and to evaluate the outcomes.The main outcomes of the transplantation of this model are seen as:a heavy accent on curative as opposed to preventive medicine which, due to the high costs of training and equipping specialized personnel has meant an astronomic increase in health spending.a medical "brain drain" towards richer countries or regions.a tendancy for the distribution of health care to be oriented towards the higher-income, highly industrialized segments of the society.a deepening of political and economic inequalities.For the purposes of comparison, the authors briefly examine another model which they term "health development". This models indicates that a general improvement in the health of the population depends as much on economic, political, ideological and technological factors as health care itself. Drawing on examples from China and Cuba, the authors note the importance of a more equitable distribution of goods, power and participation in the process of improving health. They conclude by stressing the necessity to carefully wegh the effects of importing modern medical practices.